Study on cellulose nanofibrils biological effects in different cellular models - Pinto, Fátima (2021)
Cellulose nanofibrils (CNFs), is an innovative environmental friendly material that has been incorporated into several types of materials, in both pure and composite forms and holds great promise in different fields of application. This leads to a rising level of human exposure and draws considerable concerns regarding its potential toxicity in humans, which are specially motivated by the physicochemical resemblance of cellulose nanofibrils with multi-walled carbon nanotubes and asbestos that have shown deleterious health effects. Currently, several in vitro toxicological studies have been performed with the aim of predicting health effects caused by exposure to CNFs. A literature review was performed to gather and analyse recent data regarding the potential cytotoxic, genotoxic, immunotoxic and epigenetic effects, in different in vitro cell models, triggered by the exposure to CNFs produced from vegetal biomass and consequently differing in critical physicochemical characteristics. The main findings of this review work demonstrate that different functionalization affects CNFs hydrophobicity, surface charge and chemistry, which may either facilitate or difficult the uptake and interaction of its functional groups with the cell membrane, affecting the biological responses. Generally, CNFs are not phagocytized and do not cause inflammatory response, but revealed in vitro genotoxicity. In fact, our data have shown that CNFs may induce chromosome damage in some cell models, e.g., a co-culture of epithelial lung alveolar cells and macrophages. However, more studies are required to assess CNFs toxicity and to understand the relationship between their physicochemical properties, their behaviour in biological media and mechanism of action, which are of outmost importance to predict their nanosafety.